(untitled) (Global Journal of Medical Research, 2020)
Background & Objectives: Occurrence of falls in older adults contributes to increased morbidity and mortality, exponential healthcare costs, and reduced quality of life. Utilization of outcome measures for screening and assessing fall risk in older patients contributes to reduced fall-related injuries, deaths, and healthcare costs, while promoting improved mobility and health status. The purpose of this study was to explore the utilization of outcome measures assessing balance and fall risk in patients 65 years and up within the outpatient physical therapy setting. Secondary aims included determining the most frequently used outcome measures as well as examining any associations between demographic variables and clinicians’ screening habits.